Thiopurines and their optimization during infliximab induction and maintenance: A retrospective study in Crohn's disease. Issue 4 (10th September 2020) - Luber, Raphael P; Dawson, Luke; Munari, Stephanie; Kariyawasam, Viraj C; Martin, Catherine; Gibson, Peter R; Sparrow, Miles P; Ward, Mark G
Abstract: Background and Aim: Combining therapy with a thiopurine is favored when commencing infliximab in Crohn's disease; however, the optimal 6‐thioguanine nucleotide (TGN) level and how long to continue thiopurines after induction are uncertain. We aimed to compare outcomes after induction and during maintenance in combination therapy versus infliximab monotherapy in Crohn's and to examine whether TGN levels were associated with outcomes. Methods: Crohn's patients induced with infliximab with or without concomitant thiopurines were retrospectively identified. Response to induction and clinical outcomes in subsequent 6‐month maintenance semesters were analyzed. A TGN level ≥235 pmol/8 × 10 8 red blood cells was considered therapeutic. Results: In 89 patients, response to induction was higher in combination therapy than monotherapy (74 vs 47%, P = 0.04). This benefit was only seen in patients with a therapeutic TGN (odds ratio 3.72, confidence interval 1.07–13.0, P = 0.04). Combination therapy during induction yielded a three times longer time to subsequent need for treatment escalation or treatment failure compared with monotherapy (29 vs 9 months, P = 0.01), with both therapeutic and subtherapeutic TGNs independent predictors on multivariate analysis. Among 370 semesters, there was no difference in outcomes between combination therapy and monotherapy ( P = 0.42), nor when combination semesters were stratified by therapeutic versus subtherapeutic TGN ( P = 0.56). In semester 1 only, a significantly higher remission rate was observed with therapeutic compared with subtherapeutic TGN (76% vs 33%, P = 0.02). Conclusions: Combination therapy dosed with an optimized thiopurine was superior to infliximab monotherapy for induction of response, durability of response, and clinical outcomes in the first 6 months following induction. Thereafter, combination therapy yielded no clinical advantage, supporting consideration of thiopurine withdrawal on a case‐by‐case basis.